Overexpression of CYB5R3 and NQO1, two NAD+‐producing enzymes, mimics aspects of caloric restriction. Issue 4 (28th April 2018) - Diaz‐Ruiz, Alberto; Lanasa, Michael; Garcia, Joseph; Mora, Hector; Fan, Frances; Martin‐Montalvo, Alejandro; Di Francesco, Andrea; Calvo‐Rubio, Miguel; Salvador‐Pascual, Andrea; Aon, Miguel A.; Fishbein, Kenneth W.; Pearson, Kevin J.; et al.
Summary: Calorie restriction (CR) is one of the most robust means to improve health and survival in model organisms. CR imposes a metabolic program that leads to increased stress resistance and delayed onset of chronic diseases, including cancer. In rodents, CR induces the upregulation of two NADH‐dehydrogenases, namely NAD(P)H:quinone oxidoreductase 1 ( Nqo1 ) and cytochrome b 5 reductase 3 ( Cyb5r3 ), which provide electrons for energy metabolism. It has been proposed that this upregulation may be responsible for some of the beneficial effects of CR, and defects in their activity are linked to aging and several age‐associated diseases. However, it is unclear whether changes in metabolic homeostasis solely through upregulation of these NADH‐dehydrogenases have a positive impact on health and survival. We generated a mouse that overexpresses both metabolic enzymes leading to phenotypes that resemble aspects of CR including a modest increase in lifespan, greater physical performance, a decrease in chronic inflammation, and, importantly, protection against carcinogenesis, one of the main hallmarks of CR. Furthermore, these animals showed an enhancement of metabolic flexibility and a significant upregulation of the NAD + /sirtuin pathway. The results highlight the importance of these NAD + producers for the promotion of health and extended lifespan.